Preliminary evaluation of a serious game for the dissemination and public awareness on preschool children's oral health - Ito, Cristina; Marinho Filho, Alfeu V.; Ito, Márcia; Azevedo, Marilia M.; De Almeida, Maurício Amaral (IOS Press, 2013)
This article presents the preliminary evaluation by dentists, teachers and parents of a serious game for dissemination of public awareness on preschool children's oral health. In this game, the player keeps a victory condition, while your tooth remains whole. Preliminary evaluation was performed in two parts. The first part was a questionnaire designed to evaluate the applicability of this technology and the opinions on the effectiveness of games in education and in oral health promotion. In the second part, the game is presented and an evaluation questionnaire of it is applied. This study had the participation of 115 persons. There was 80% approval which suggested that the game is an alternative for the prevention of dental awareness. Furthermore, the study perceives that teachers can work together with dentists in order to perform dental prevention. © 2013 IMIA and IOS Press.
Keywords: Dental Education; Medical Informatics; Oral Health; Video Games